Zorotypus weiweii (Zoraptera: Zorotypidae), a new species of angel insects, from Sabah, East Malaysia - Wang, Jianyun; Li, Hu; Cai, Wanzhi (Zootaxa, 2016)
A new species of the insect order Zoraptera, Zorotypus weiweii, is described and figured from Sabah, East Malaysia. The new species represents the second angel insect from Borneo. Z. caudelli Karny was also collected near the type locality of Z. weiweii. Methods of specimen collection and a brief note of angel insects in Malaysia were provided based on new materials and biological observations.